2020
DOI: 10.3390/antiox9070615
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Rescues Motor Neuronal Toxicity in Fly Model of Amyotrophic Lateral Sclerosis

Abstract: Transactive response DNA-binding protein-43 (TDP-43) is involved in the pathology of familial and sporadic amyotrophic lateral sclerosis (ALS). TDP-43-mediated ALS models in mice, Drosophila melanogaster, and zebrafish exhibit dysfunction of locomotor function, defective neuromuscular junctions, and motor neuron defects. There is currently no effective cure for ALS, and the underlying mechanisms of TDP-43 in ALS remain poorly understood. In this study, a genetic screen was performed to identify modifiers of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Pan-neuronal overexpression of TDP-43 or TBPH induced premature lethality [ 266 , 274 , 275 , 306 , 307 ], reduced lifespan [ 266 , 305 , 309 , 310 ], larval locomotion defect [ 266 ], and age-dependent climbing deficit [ 309 , 311 ]. Similar phenotypes were observed when TBPH or TDP-43 was expressed in motoneurons [ 265 , 273 , 275 , 289 , 290 , 293 , 302 , 305 , 306 , 313 , 315 , 316 , 317 , 318 , 319 , 320 , 322 , 323 ]. By using the temporal and regional gene expression targeting (TARGET) system, it was shown that adult-restricted overexpression of TBPH or TDP-43 in all neurons or motoneurons induced age progressive climbing defects and reduced lifespan [ 288 , 301 , 305 , 307 , 312 , 324 ].…”
Section: Tdp-43 Proteinopathy In the Fruit Flysupporting
confidence: 66%
See 4 more Smart Citations
“…Pan-neuronal overexpression of TDP-43 or TBPH induced premature lethality [ 266 , 274 , 275 , 306 , 307 ], reduced lifespan [ 266 , 305 , 309 , 310 ], larval locomotion defect [ 266 ], and age-dependent climbing deficit [ 309 , 311 ]. Similar phenotypes were observed when TBPH or TDP-43 was expressed in motoneurons [ 265 , 273 , 275 , 289 , 290 , 293 , 302 , 305 , 306 , 313 , 315 , 316 , 317 , 318 , 319 , 320 , 322 , 323 ]. By using the temporal and regional gene expression targeting (TARGET) system, it was shown that adult-restricted overexpression of TBPH or TDP-43 in all neurons or motoneurons induced age progressive climbing defects and reduced lifespan [ 288 , 301 , 305 , 307 , 312 , 324 ].…”
Section: Tdp-43 Proteinopathy In the Fruit Flysupporting
confidence: 66%
“…This indicates that the level of TDP-43 must be tightly regulated throughout life. GOF experiments also revealed that excess of TBPH or TDP-43 is highly toxic in muscles [ 270 , 306 , 307 ], glial cells [ 270 , 307 , 309 , 325 , 326 ], and in the eye [ 266 , 274 , 289 , 290 , 292 , 293 , 302 , 303 , 304 , 306 , 307 , 310 , 312 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 324 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 ]. Moreover, it was reported that TBPH or TDP-43 overexpression induces cell death, as was shown in motoneurons [ 266 , 289 , 290 , 301 ], glial cells [ 309 , 326 ], mushroom bodies [ 265 , 290 ], and in the eye.…”
Section: Tdp-43 Proteinopathy In the Fruit Flymentioning
confidence: 99%
See 3 more Smart Citations